Ghost-hunting - Bagans, Zak, 1977- (--For dummies., 2020)
"Dive into the ghostly world of the supernatural with America's leading paranormal investigator. Inside, paranormal investigator, star, and executive producer of The Travel Channel's hit series, Ghost Adventures and founder of the award-winning Haunted Museum (Las Vegas' most popular attraction), Zak Bagans takes readers on an exciting journey into the supernatural world. With insider information on the history of ghost-hunting to learning about ghosts with all kinds of temperaments, Ghost-Hunting For Dummies is peppered with true accounts and stories from Bagans' famous cases and investigations. Featuring expert advice on picking a haunted location, setting up cameras, and dealing with unwieldy ghosts, this book shows how today's investigators use the tools of modern science to study a wide range of paranormal activity"--